Hi Jared,

When you multiply a term by zero, the answer is zero.

So set each of the factors to be equal to zero and solve for the variable.

7y - 8 = 0

7y = 8

y = 8/7

Now you can do the same for the second factor.

Have fun.

Dan

Jared G.

asked • 02/29/16Solve the following equation for the indicated variable:

(7y-8)(2y+7)=0

(7y-8)(2y+7)=0

Hint: This equation is already in factored form, so use the Zero-Factor Property to set each of the factors equal to 0.

Follow
•
2

Add comment

More

Report

Hi Jared,

When you multiply a term by zero, the answer is zero.

So set each of the factors to be equal to zero and solve for the variable.

7y - 8 = 0

7y = 8

y = 8/7

Now you can do the same for the second factor.

Have fun.

Dan

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.